2014
DOI: 10.1002/ijc.28907
|View full text |Cite
|
Sign up to set email alerts
|

Potent and specific antitumor effect of CEA‐targeted photoimmunotherapy

Abstract: Conventional photodynamic therapy (PDT) for cancer is limited by the insufficient efficacy and specificity of photosensitizers. We herein describe a highly effective and selective tumor-targeted PDT using a near-infrared (NIR) photosensitizer, IRDye700DX, conjugated to a human monoclonal antibody (Ab) specific for carcinoembryonic antigen (CEA). The antitumor effects of this Ab-assisted PDT, called photoimmunotherapy (PIT), were investigated in vitro and in vivo. The Ab-IRDye conjugate induced potent cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 35 publications
4
79
0
Order By: Relevance
“…NIR-PIT appears to specifically kill target cells while leaving adjacent normal cells unharmed (15)(16)(17). Although NIR-PIT has been primarily tested with antibodies directed at cancer antigens, it can also be used to kill cells of any type for which there is an appropriate antibody (18)(19)(20). Therefore, NIR-PIT could also be used to deplete a selected subpopulation of immune cells within the tumor tissue.…”
Section: Introductionmentioning
confidence: 99%
“…NIR-PIT appears to specifically kill target cells while leaving adjacent normal cells unharmed (15)(16)(17). Although NIR-PIT has been primarily tested with antibodies directed at cancer antigens, it can also be used to kill cells of any type for which there is an appropriate antibody (18)(19)(20). Therefore, NIR-PIT could also be used to deplete a selected subpopulation of immune cells within the tumor tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The target cell type can be adapted with various APC. Various antibodies or antibody fragments, including anti-EGFR, anti-PSMA, anti-mesothelin, and anti-CEA were already used as APCs [15][16][17][18][19][20][21] . Additionally, changing the region of NIR-irradiation can minimize the region treated.…”
Section: Discussionmentioning
confidence: 99%
“…During the exposure to NIR-light, the cellular membrane ruptures leading to cell death [9][10][11][12][13][14] . NIR-PIT has proven to be effective with multiple antibodies or antibody fragments, including anti-EGFR, anti-HER2, anti-PSMA, anti-CD25, anti-mesothelin, anti-GPC3, and anti-CEA [15][16][17][18][19][20][21] . Therefore, NIR-PIT can be used against a wide variety of target molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In the NIR-PIT group the volume of 3T3/HER2 cells increased gradually after NIR light exposure although it did not reach significance. Within minutes, cells treated with NIR-PIT rapidly increase in volume leading to rupture of the cell membrane, and extrusion of cell contents into the extracellular space [2][3][4][5] indicating a necrotic rather than apoptotic cell death [6][7][8]. Therefore, the rapid increase in 3T3/HER2 cell volume indicated that NIR-PIT induces necrotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…NIR light exposure at 690 nm induces nearly immediate cell necrosis characterized by severe damage to the cell membrane. This mechanism of cell death stands in contrast to traditional photodynamic therapy in which a lipid soluble porphyrin derivative enters the cell and causes damage to the mitochondria resulting in an apoptotic cell death [2][3][4][5]. Cells treated with NIR-PIT undergo rapid volume expansion leading to rupture of the cell membrane and extrusion of cell contents into the extracellular space.…”
Section: Introductionmentioning
confidence: 99%